ACCELERATING INNOVATION ACTIVITIES OF PRIVATE BUSINESSES - Nabiyeva Muhabbat Jabirhanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article examines factors for enhancing the innovative activities of business entities.